Exercise in the treatment of alcohol dependence - Eraslan, Defne; Kanyılmaz, Selcen; Öztürk, Özgür (Journal of Dependence, 2014)
In recent years, psychiatrists have started to consider exercise as a useful add on to treatment in different psychiatric conditions and studies have been planned to measure its effect. In the treatment of alcohol dependency, alternative treatment plans that could provide longer periods of abstinence and help overcome the physical problems caused by alcohol are needed. Given its psychological and physiologic benefits in areas such as mood, dopaminergic system and sleep, exercise can be a useful technique in the treatment of alcohol related problems. However, there are very few clinical studies that focus on the use of exercise in alcohol dependency. This paper aims to review current data on exercise and alcohol related problems and find directions for future research.